Prevalence of Prediabetes in Adolescents - Firdawsyi Nuzula; Maulida Oktaviana; Hasriwiani Habo Abbas (Fakultas Kesehatan Masyarakat Universitas Muslim Indonesia, 2025)
Prediabetes is closely associated with an increased risk of adult-onset diabetes, and the risk is even greater when it occurs in adolescence. Prediabetes is increasing globally across all age groups, including children and adolescents, increasing significantly with age and is particularly common in adolescents with obesity, inactivity, and unhealthy lifestyles. Prevention of cases in children includes lifestyle programs, reducing weight, changing diet, and increasing physical activity. The purpose of the study was to analyze the prevalence of prediabetes in adolescents. This research is a quantitative method, observational research with a cross-sectional design; the research population is first-year students of the Russian College of Health Sciences, and the sampling technique is a total sampling of 115 respondents. The variables studied were diet, physical activity, stress, fast food, and prediabetes. The results showed the value of genetic influence with prediabetes p value = 0.002, BMI with no influence with prediabetes p value = 0.158, no influence of physical activity with prediabetes p value = 0.310, no influence of diet with p-value = 0.863, no influence of stress with prediabetes in adolescents p value = 0.580. There is no influence of active/passive smoking habits with prediabetes p value = 0.653. Genetic and environmental factors among ethnic groups can contribute to increasing the risk of prediabetes or type 2 diabetes and early hypertension. Conclusion: The results showed that only one genetic variable influenced prediabetes in adolescents.